EVALUASI PROGRAM RUMAH PADAT KARYA VIADUCT BY GUBENG DI KECAMATAN GUBENG - Sukma, Dini Artika; Zamba, Marisca Trianita; Arsadi, Sabillah Dewi Wahyu Rizqika; Salsabila, Diah Arini; Anisykurlillah, Rosyidatuzzahro (Jurnal Publik, 2025)
The Viaduct by Gubeng Labor-Intensive Housing Program was initiated by the government as an effort to address the socio-economic impacts following the Covid-19 pandemic, particularly for the poor communities in Surabaya City. This program offers labor-intensive training and employment to improve welfare and reduce dependence on direct assistance. This study aims to evaluate the implementation of the Viaduct by Gubeng program using the CIPP evaluation model, which includes context, input, process, and product dimensions. The method employed is descriptive qualitative with data collection techniques such as interviews, observations, and documentation. The results indicate that the program successfully targets the appropriate groups and effectively reduces unemployment rates. The program has also utilized assets and funds efficiently, however, challenges remain regarding participant work motivation, an inadequate incentive system, and limited evaluation and two-way communication. Overall, Viaduct by Gubeng is considered innovative and worthy of being a model for empowerment programs but still requires improvements in human resource management and worker welfare to ensure the program’s long-term sustainability.